2008
DOI: 10.1186/1471-2474-9-171
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time-to-surgery on outcome in elderly patients with proximal femoral fractures

Abstract: Background: Whether reducing time-to-surgery for elderly patients suffering from hip fracture results in better outcomes remains subject to controversial debates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
3
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 24 publications
9
97
3
15
Order By: Relevance
“…Functional status before fracture, older age, male gender, and higher surgical risk increased the risk of mortality, whereas the use of antibiotics and physical therapy after surgery decreased the risk. Previous studies showed functional status before fracture [14,42,45,52], male gender [12,15,28,33,36,42,47], older age [10,15,28,36,43,47,50,52,55], and higher ASA scores predicted mortality in older patients [24,26,33,44,49] (Table 3), which is in agreement with our findings. In our study, we did not see a difference in mortality between patients undergoing arthroplasty versus patients undergoing osteosynthesis, which is in agreement with mortality reported by Garcia et al [15] and others [18,33,37].…”
Section: Discussionsupporting
confidence: 83%
“…Functional status before fracture, older age, male gender, and higher surgical risk increased the risk of mortality, whereas the use of antibiotics and physical therapy after surgery decreased the risk. Previous studies showed functional status before fracture [14,42,45,52], male gender [12,15,28,33,36,42,47], older age [10,15,28,36,43,47,50,52,55], and higher ASA scores predicted mortality in older patients [24,26,33,44,49] (Table 3), which is in agreement with our findings. In our study, we did not see a difference in mortality between patients undergoing arthroplasty versus patients undergoing osteosynthesis, which is in agreement with mortality reported by Garcia et al [15] and others [18,33,37].…”
Section: Discussionsupporting
confidence: 83%
“…Delayed surgery could also be associated with not only mortality but also increased risk of pneumonia and pressure sores [5]. Smektala et al also emphasize that time to surgery does not decrease mortality in elderly patients but somewhat lowers the rates of complications due to immobility [15]. We found in patients that were operated after 72 hours, time to theatre is not related with mortality.…”
Section: Discussionsupporting
confidence: 51%
“…Delay of surgery more than 48 hours after the fracture has been associated with increased mortality [27,28] but mostly for a delay exceeding 48 hours after the fracture.…”
Section: Discussionmentioning
confidence: 99%